Lamenting Tyre (Ezekiel 27) A Unique Perspective on Judah's Proximate Other - Leonard-Fleckman, Mahri (2022)
This article explores the distinct portrayal of Tyre in the קינה or lament of Ezekiel 27 and its literary-historical relationship to the cycle as a whole. I propose that the קינה is a conceptually independent source around which the Tyre cycle was shaped. By underscoring both the unique perspective of the lament and how it is reimagined within the prophecies regarding Tyre, my goal is to deepen our understanding of the complex relationship between Tyre and Judah as depicted in the varied portrayals of Ezekiel 26-28.